The Impact of Work Motivation, Organizational Commitment, and Compensation on OCB: A Study in Public Relations and Protocols of BNN Indonesia - Galih Citra Kumala; Wisudani Rahmaningtyas (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
Organizational Citizenship Behavior (OCB) is closely related to organizational performance and encompasses employee behaviors that support organizational effectiveness. These include social competence to maintain team cohesion, willingness to participate in collaborative efforts to achieve collective goals, and the ability to maintain moral and psychological balance in achieving personal and organizational objectives without harming others. OCB plays a crucial role in enhancing or diminishing organizational performance. The population in this study consisted of 56 employees from the Public Relations and Protocol at the BNN Indonesia. The sampling technique used was a saturated sampling method, in which the entire population was included as the sample. This study applied a quantitative research approach, with data collected through questionnaires. The data were then analyzed using multiple regression analysis with IBM SPSS Statistics version 29. The findings revealed that work motivation, organizational commitment, and compensation simultaneously have a positive and significant influence on Organizational Citizenship Behavior. Furthermore, the partial analysis indicated that each independent variable—work motivation, organizational commitment, and compensation—individually exerts a positive and significant effect on OCB. These findings align with the principles of Social Exchange Theory, which posit that reciprocal relationships between individuals and their institutions encourage voluntary contributions beyond formal job responsibilities.